PROFIL PERMASALAHAN YANG DIALAMI LANSIA DI RT.1 RW.1 KELURAHAN ANDALAS KECAMATAN PADANG TIMUR KOTA PADANG. - -, Herayani - (Bimbingan dan Konseling, 2014)
This research is motivated by the problems experienced by the elderly to grow old. This study aimed to determine and describe the profile of the problems experienced by the elderly, with a focus on research that profiles the problems experienced by the elderly in the village RW.1 RT.1 Andalas Padang Padang District East in terms of the physical, psychological and social. This research was conducted with a qualitative descriptive approach that describes the symptoms, facts and reality on the ground as it is. The informants consisted of three key informants and six additional informant. The instruments used were observation, interview and documentation. Techniques used in data processing is data reduction, data presentation, and conclusion. Results of the study revealed that the elderly have problems in serving his parents, because it was not ready for the old days with a variety of physical problems, psychological and social issues faced. Based on this research, it was recommended to the elderly as well as related parties to be able to overcome the problems found.